What drives policy change? Evidence from six empirical applications of the kaleidoscope model - Haggblade, Steve (2017)
Steve Haggblade POLICY SEMINAR What Drives Policy Change? Insights from the Kaleidoscope Model of Food Security Policy Organized by IFPRI, Michigan State University and University of Pretoria, Consortium partners- Food Security Policy Innovation Lab